The Relationship between Training and emotional Intelligence: A Discovery study in the Ministry of Higher Education and Scientific Research - Amaar Abdul Al lateef (Iraqi Journal for Administrative Sciences, 2024)
Training is a subject which takes little care from organization managers and Leaders because of their traditional point of view toward it and the absence of the social and psychological aspects concerning the management fields in general and training in particular for this reason the importance of research emerges about the relationship between training and emotional intelligence learning so as to enable persons and organizations to benefit from training. Training resembles one of the main and important stages of learning the emotional intelligence. The research paper intends to link between training and learning the emotional intelligence and resembles an attempt to improvement and development of information and skills and capacities of the affecting forces in organization, and to manifest the training role and influences upon persons in particular and organizations in general as well as clarifying the matters of intelligence and emotion and emotional intelligence and be familiar with stages and processes of learning the emotional intelligence in general and training in particular. The research paper concluded to a main conclusion namely: that the emotional intelligence is important factor in the success of persons in personal level and the work field inside the organization as well as the social life and this depends upon the presence of good and drastic training to achieve that.